Does task technology fit, social influence, and habit impact on actual usage of mobile banking in Indonesia? - Rafisya Arinda Pramesti; Nur Afifah; Erna Listiana; Wenny Pebrianti; Ana Fitriana (Institute of Computer Science (IOCS), 2023)
Currently, technological developments are increasingly rapid due to digitalisation. Digitalisation has caused several phenomena that encourage community activities, including the cashless society phenomenon. The implementation of mobile banking in cashless transactions in the cashless society phenomenon is driven by several factors. This research was conducted to determine the influence of task technology fit, social influence, and habit on cashless behavioural intention and impacts on actual usage of BNI Mobile Banking in Indonesia. This research adopts the UTAUT 2 and Task Technology Fit model theories. This research is a quantitative research with 236 respondents. The research measurement model was analysed using Structural Equation Modeling (SEM) and the AMOS 22 statistical tool. The findings of this study show that task technology fit, social influence, and habit all positively impact people's intention to implement cashless behaviour, which positively impacts the actual usage of BNI Mobile Banking. Cashless behavioural intention can also mediate task technology fit, social influence and habit on actual usage of BNI Mobile Banking. Through digital and mobile banking solutions, this research supports the marketing strategy of the banking industry to turn Indonesia towards a cashless society by 2030.